In the House - Kilpatrick, Lynn K. (Lynn Kathleen) (Book collections on Project MUSE., 2010)
In Lynn K. Kilpatrick's In the House, anything can happen. A collection of shortslists, character sketches, directions, scripts, and instructionsIn the House reveals the often conspicuous, yet frequently overlooked, dangers of relationships gone awry. In a home suffused with fragility or in a kitchen surrounded by knives, Kilpatrick's men and women navigate around one another's eccentricities with caution, highlighting the unspoken desires and veiled needs of domestic routine. In these stories those desires collide, illuminating the dangers that can lurk in seemingly insignificant places suc.